Enhanced diagnostic capabilities of thromboelastography coupled with standard coagulation indices for predicting perioperative thrombosis in older individuals with hip fractures - Huan Yang; Yusong Yuan; Lei Shi; Yurun Yang; Yidan Zhu; Ying Chen (Journal of Orthopaedic Surgery and Research)
Abstract Background Deep venous thrombosis of the lower extremity is a common and fatal complication of hip fracture in the elderly. However, there is a lack of targeted laboratory diagnostic methods. Although traditional laboratory indicators can provide some reference, the diagnostic efficiency is relatively limited This study aimed to investigate the diagnostic accuracies of thromboelastography (TEG) combined with traditional coagulation parameters for early diagnosis of newly occurring lower extremity deep vein thrombosis (DVT) in elderly patients with hip fractures. Methods We conducted a retrospective cohort study including seventy-four elderly patients with hip fractures without lower extremity DVT at admission between 2022 and 2023. Disease history, laboratory tests including blood routine, six coagulation parameters at admission, and TEG on the day after the operation were collected using validated methods. Color Doppler ultrasonography of lower extremity venous was performed at admission and discharge to confirm the diagnosis of perioperative new thrombosis. A logistic regression model was used to construct joint diagnostic indexes using traditional parameters, including coagulation parameters and patient histories, combined with TEG indicators, and the receiver operating characteristic (ROC) curve was used to evaluate the discriminatory ability of each single TEG indicator and joint diagnostic indicators for newly occurring thrombosis in elderly patients with hip fracture. Results The incidence of lower extremity DVT was 33.78%. The average age was 82.0 years, and 7.0% were male. The TEG R values at discharge were 5.8 min and 6.3 min for the DVT and without VTE groups, respectively, showing a significant difference (p = 0.035). D-dimer levels in the DVT group were significantly higher than in the non-VTE group (4.3 vs. 2.9 mg/L, p = 0.029). The multivariate-adjusted model showed significant correlations between newly occurring DVT and TEG indicators, including R values, D-dimer, and BMI, with odd ratio values of 0.43, 1.43, and 1.25, respectively (all p value < 0.05). Among each traditional coagulation parameter and TEG indicators, D-dimer and R-value had the highest diagnostic accuracy (ROC area under the curve, AUC for D-dimer: 67.7%; AUC for R: 67.6%), respectively. For joint indicators, the combination of R + CI + αangle + D-dimer had the highest AUC (0.7475), followed by R + CI + αangle + BMI (0.7123). R + CI + αangle + gender had the lowest AUC (0.5920). Conclusion TEG demonstrates diagnostic value for newly occurring lower extremity DVT in elderly hip fracture patients. When combined with traditional coagulation parameters and patient histories, its diagnostic value is further enhanced, providing robust support for the establishment of a more comprehensive diagnostic and predictive scoring system for DVT in elderly hip fracture patients.